(untitled) (مجلة الواحات للبحوث والدراسات, 2026)
This study provides a thorough critical analysis of the historical-critical method as applied to the Qur’an. It focuses specifically on the works of the Belgian researcher Guillaume Dye, published in the Qur’an of Historians, which is presented as a prime example of contemporary Orientalist trends. The study aims to examine the methodological foundations and preconceived assumptions underlying this approach and evaluate the validity of its main hypotheses regarding the origin and formation of the Qur’anic text. It concludes that Dye’s application of the historical-critical method suffers from structural imbalances stemming from prior philosophical assumptions (e.g. the rejection of divine revelation), the systematic marginalisation of Islamic sources and the imposition of interpretative models derived from textual studies without considering the fundamental differences between the Qur’an and the Bible. Furthermore, the study emphasises that the available material evidence (manuscripts and archaeological inscriptions) corroborates the traditional Islamic narrative concerning the early compilation of the Qur’an and its textual stability. The Qur’an is not subjected to scientific scrutiny that respects its methodological uniqueness, nor are all sources dealt with according to equal critical standards.